Neutralizing Monoclonal Antibodies against Disparate Epitopes on Ricin Toxin’s Enzymatic Subunit Interfere with Intracellular Toxin Transport - Yermakova, Anastasiya (Sci Rep, 2016)
Ricin is a member of the A-B family of bacterial and plant toxins that exploit retrograde trafficking to the Golgi apparatus and endoplasmic reticulum (ER) as a means to deliver their cytotoxic enzymatic subunits into the cytoplasm of mammalian cells. In this study we demonstrate that R70 and SyH7, two well-characterized monoclonal antibodies (mAbs) directed against distinct epitopes on the surface of ricin’s enzymatic subunit (RTA), interfere with toxin transport from the plasma membrane to the trans Golgi network. Toxin-mAb complexes formed on the cell surface delayed ricin’s egress from EEA-1(+) and Rab7(+) vesicles and enhanced toxin accumulation in LAMP-1(+) vesicles, suggesting the complexes were destined for degradation in lysosomes. Three other RTA-specific neutralizing mAbs against different epitopes were similar to R70 and SyH7 in terms of their effects on ricin retrograde transport. We conclude that interference with toxin retrograde transport may be a hallmark of toxin-neutralizing antibodies directed against disparate epitopes on RTA.